Effect of N,P,K Fertilizer Rate and Biofertilizer on Growth and Yield of Grendel Rice Variety - Qhodarisman, Dedy; Budiasih, Budiasih; Budiono, Heru (Institute of Computer Science (IOCS), 2023)
The research was carried out in the rice fields of Jaya Mukti Village, Blanakan District, Subang Regency, with a height of 10 meters above sea level and a type of rainfall (Appendix 1). The trial will be carried out from August 2022 to November 2022. This study aims to learn about the interaction of the influence of N, P, K fertilizer and biological fertilizer doses on the growth and yield of Grendel rice paddy crops. This experiment uses a Random Group Design (RAK) experimental design of a factorial pattern consisting of two factors, the first factor is 3 levels of N, P, K (p) fertilizer and the second factor is Biological Fertilizer (h) as many as 3 levels, both factors are repeated 3 times. There were 9 treatment combinations that were randomly placed on each replicate. The results of the study showed that the administration of N, P, K fertilizer and biological fertilizer had an effect on growth (plant height 21 DAP and number of saplings 28 DAP), yield (grain weight per clump). The application of N, P, K fertilizer has an effect on the yield components (number of productive saplings, panicle length and weight of 1000 grains). The N,P,K dose of 60 % indicates the best panicle length and weight of 1000 grains. A dose of 30 kg ha -1 biofertilizer showed good results on plant growth